INTERPRETASI DAN IMPLEMENTASI WAHYU DALAM ISLAM - Hilman Nafian; Indo Santalia (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2022)
Al-Revelation (revelation) is the word masdar (infinitive). He points to two basic meanings: hidden and fast. Therefore, it is said